2017
DOI: 10.3171/2016.8.spine16462
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of spinal osteoid osteoma: a prospective study

Abstract: OBJECTIVE Surgery has been considered the standard treatment for spinal osteoid osteomas that are refractory to analgesic agents. Radiofrequency ablation (RFA) is a less invasive technique with established efficiency for the treatment of peripheral osteoid osteomas. The main objectives of this study are to evaluate the safety of RFA based on the results of a previous experimental study in rats conducted in the authors' laboratory and to identify its short- and long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
(21 reference statements)
1
7
0
1
Order By: Relevance
“…The approach to the cyst and the synovium with RF has not been addressed before this report. Recent studies have shown that RF current can safely be used intra-spinally, around the lumbar nerve roots, and within the contiguous vertebrae as long as the patient can undergo motor and sensory testing [6, 25]. In our longest clinical followup of three years, we confirmed with sequential MRI scans that there was a reduction and stabilization of a large dorsal cyst without re-accumulation or re-expansion.…”
Section: Discussionsupporting
confidence: 64%
“…The approach to the cyst and the synovium with RF has not been addressed before this report. Recent studies have shown that RF current can safely be used intra-spinally, around the lumbar nerve roots, and within the contiguous vertebrae as long as the patient can undergo motor and sensory testing [6, 25]. In our longest clinical followup of three years, we confirmed with sequential MRI scans that there was a reduction and stabilization of a large dorsal cyst without re-accumulation or re-expansion.…”
Section: Discussionsupporting
confidence: 64%
“…No chemotherapy after surgery is recommended. Radiofrequency ablation may be considered when complete surgical excision is not possible (Soltero-Rivera et al 2015;Faddoul et al 2016). Another treatment which is technically feasible in human medicine is image-guided cryoablation (Whitmore et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It mainly involves the lumbar spine with predilection for posterior elements seen in 75% of cases. [ 1 , 2 ] Pars interarticularis is the most common site of involvement. OOs are usually seen in patients under the age of 30 with a male preponderance (sex ratio – 2–4:1).…”
Section: Discussionmentioning
confidence: 99%